A Transient UWB Antenna Array Used with Complex Impedance Surfaces - A. Godard; L. Desrumaux; V. Bertrand; J. Andrieu; M. Lalande; B. Jecko; V. Couderc; M. Brishoual; R. Guillerey (International Journal of Antennas and Propagation)
The conception of a novel Ultra-Wideband (UWB) antenna array, designed especially for transient radar applications through the frequency band (300 MHz–3 GHz), is proposed in this paper. For these applications, the elementary antenna must be compact and nondispersive, and the array must be able to steer in two dimensions. The geometry of the elementary antenna and its radiation characteristics are presented. The array beam steering is analyzed and a technique making the increase of the transient front-to-back ratio possible is described.